Integrated Biomaterials Science - Barbucci, Rolando. (Springer US, 2002)
Integrated Biomaterials Science provides an intriguing insight into the world of biomaterials. It explores the materials and technology which have brought advances in new biomaterials, highlighting the way in which modern biology and medicine are synergistically linked to other key scientific disciplines-physics, chemistry, and engineering. In doing so, Integrated Biomaterials Science contains chapters on tissue engineering and gene therapy, standards and parameters of biomaterials, applications and interactions within the industrial world, as well as potential aspects of patent regulations. Integrated Biomaterials Science serves as a comprehensive guide to understanding this dynamic field, yet is designed so that chapters may be read and understood independently, depending on the needs of the reader. Integrated Biomaterials Science is attractive to a broad audience interested in a deeper understanding of this evolving field, and serves as a key resource for researchers and students of biomaterials courses, providing all with an opportunity to probe further.